Developing co-operative education in the built environment through post occupancy evaluation of DETE educational facilities : Final Report. - Alderman, Lyn (Office for Learning and Teaching, 2016)
Co-operative education, where students acquire professional knowledge, skills and attitudes, offers a supportive pathway from study to employment. This pilot will establish an ongoing Co-operative Education Centre to offer paid WIL opportunities to built environment students to conduct Post Occupancy Evaluations (POEs) on DETE educational facilities. Pre-professional students will conduct applied research, this will then increase the usability of POEs results, which in turn provide a results database to inform DETE educational building design standards, and ultimately future research into the relationship between learning outcomes and the built environment. As POEs are a recognised employment activity, DETE will fund the employment with QUT as the broker and this elevates students' WIL to sustainable co-operative education. This pilot developed a prototype mobile app to aid in the consistent data collection and storage of information arising from the POEs. Ultimately, curriculum renewal is informed by both academic and student feedback arising from these applied research opportunities.